Results of Routine Antenatal Screening for Cytomegalovirus at a Tertiary Center - Duygu TUGRUL ERSAK; Izzet OZGURLUK; Ayse Gulcin BASTEMUR; Esra GULEN YILDIZ; Selcan SINACI; Ezgi TURGUT; Ozgur KARA; Atakan TANACAN; Dilek SAHIN (Medeniyet Medical Journal)
Objective: Cytomegalovirus (CMV) is the most common viral infection. In this study, we discussed the results of pregnant women who underwent antenatal CMV screening in a tertiary center and the value of CMV antenatal screening. Methods: For this retrospective study, the data of pregnant patients with antenatal CMV screening test results between 2019 and 2022 were obtained from hospital records. CMV immunoglobulin M (IgM), CMV IgG, anti-IgG avidity test results, amniocentesis, CMV polymerase chain reaction (PCR), and the outcome of the babies were recorded. Results: A total of 31,912 CMV IgM and 26,969 CMV IgG tests were performed. CMV IgG seropositivity was observed in 78.99% of pregnant women, and 0.09% of the pregnant women were confirmed to have a positive CMV IgM test result. Pregnant women with positive IgM accompanying low avidity were referred to perinatology clinics for detailed ultrasonography and amniocentesis. Only 3 of the 44 pregnant women who underwent amniocentesis were confirmed to have positive CMV PCR testing. Conclusions: CMV screening should be preserved for pregnant women with ultrasonographic findings at high risk of congenital CMV infection.